Dostęp MSP do venture capital - Koszałka-Frank, Izabela (Small and Medium Enterprises' Access to Venture Capital, 2008)
The paper concerns some selected issues of venture capital and private equity. The concepts of venture capital and private equity have been presented, as well as the significance of this institution for the development of new and innovative transactors and for the increase in competitiveness of the Polish economy. The origin and perspectives of the development of VC/PE market in Poland and developed countries have been outlined. Moreover, the factors inhibiting the development of this finance source have been indicated.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 322-331